Hans Gammeltoft-Hansen, Jon Andersen, Kaj Larsen og Karsten Loiborg, Forvaltningsret, København: Jurist- og Økonomforbundets Forlag, 1994, 714 s., kr. 775,00. - Peter Christensen, Jens (Politica, 1994)
-